Thinking about the Miraculous with Schleiermacher: Pentecostalism and the Eternal Covenant between Faith and Science - Morrison, Stephen D. (Pneuma, 2026)
This article proposes a modern way to think about the miraculous for Pentecostal theology, one that retains the livingness of the God who is active in the Church without asking believers to reject the results of scientific inquiry. It argues constructively from Friedrich Schleiermacher's model for understanding the supernatural to interpret miracles naturally without denying either their edifying power or the possibility of divine origins. The specific example of prophetic ministry is considered here but with implications for broader charismatic practices.